Sustainable Long-Term Energy Supply and Demand: The Gradual Transition to a New and Renewable Energy System in Indonesia by 2050 - Yudiartono Yudiartono; Jaka Windarta; Adiarso Adiarso (International Journal of Renewable Energy Development, 2023)
The objective of this work is to evaluate long-term energy demand and supply decarbonization in Indonesia. On the demand side, electric vehicles and biofuels for transportation and induction stoves and urban gas networks for households were considered. Based on the National Energy Policy, primary energy supply projections optimized NRE power plant use and increase NRE's position in the national energy mix. A Low Emissions Analysis Platform (LEAP) model evaluates 2020–2050 energy demand predictions and low-carbon energy systems. This study's sustainable transition options require two basic technical advances. First, electric vehicles and induction stoves would reduce oil fuel usage by 228.34 million BOE and LPG consumption by 24.65 million BOE. Second, power generation should be decarbonized using NRE sources such as solar, hydro, biomass, geothermal, and nuclear. In 2050, solar power (40 GW), hydropower (38.47 GW), geothermal power (10 GW), and other NRE (24.45 GW, 18.67 GW of which would be biomass power) would dominate NRE electrical capacity. Biomass co-firing for coal power plants would reach 36.35 million tons in 2050. In 2035, the Java-Bali or West Kalimantan system will deploy 1 GW of nuclear power reactors, rising to 4 GW by 2050. Under the Transition Energy (TE) scenario, by 2025 and 2050, new and renewable energy would make up 23% and 31% of the primary energy mix, respectively, reducing GHG emissions per capita. According to predictions, annual GHG emissions per capita will decline from the BAU scenario's 4.48 tonne CO2eq/capita in 2050 to the TE scenario's 4.1 tonne.